Pyridine-2-thiolate bridged tin-palladium complexes with Sn(PdN2Cl2), Sn(PdN2S2), Sn(PdN2C2) and Sn(Pd2N4) skeletons - Waechtler, Erik; Gericke, Robert; Zhechkov, Lyuben; Heine, Thomas; Langer, Thorsten; Gerke, Birgit; Poettgen, Rainer; Wagler, Joerg (Chemical Communications, 2014)
Reactions of tin(IV) complexes of the type Sn(PyS)2X2 (X = Cl, PyS, Ph; PyS = pyridine-2-thiolate) with Pd(PPh3)4 provide easy access to novel heterometallic complexes with Pd-Sn bonds. Electronic characteristics of this connection were analysed by X-ray crystallography, 119Sn Mössbauer spectroscopy and quantum chemical analyses. © 2014 Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20